Periodontal tratment and drug-induced gingival hyperplasia: Systematc literature review (Research, Society and Development, 2023)
Gingival hyperplasia is an abnormal growth of the gingival tissue, which may start in the anterior gingival tissues and then move on to affect the entire posterior part. In some cases, the gums can hyperplasia and compromise almost the entire tooth surface. Faced with the need to obtain targeted information with up-to-date evidence on the indications and effectiveness of the treatment of hyperplasia, this study aimed to carry out a systematic review of the literature on periodontal treatment and drug-induced gingival hyperplasia. Search strategies were constructed for each of the following databases: PubMed, Embase, Scopus and LiLACS. The gray literature search was performed on Pubmed Central. The keywords used were Periodontitis, Periodontal Desease, Gingival hyperplasia drug, Cyclosporine, Phenytoin, periodontal treatment, periodontal parameters. The search totaled 675 studies. After removing duplicates and considering the eligibility criteria, 5 studies were selected for this systematic review. The risk of bias was assessed independently by two review authors. The RevMan Software was used to generate the summary and graph of the risk of bias of the selected studies that patients who use drugs that induce gingival hyperplasia are followed up by a dental surgeon, since several studies state that no matter how much a hygiene correctly, gingival enlargement will almost always occur. According to the development of the case, it may even undergo some surgical procedures, such as gingivoplasty or a gingivectomy.